Universitas sebagai Organisasi Pembelajaran: Studi Kasus di Universitas Islam Negeri Jawa Timur Indonesia (IAI Sunan Giri Trenggalek, 2025)
In line with the spirit of political reform in Indonesia, the flow of educational reform in Indonesia has also changed drastically. The education system in Islamic universities as the highest educational institution has changed from centralized from the center to an institution that carries the principle of campus autonomy. With this new paradigm, universities have full authority to manage administrative management, education systems and others to advance professional institutions and produce competent students. The purpose of this study is to critically analyze the application of the Learning Organization (OP) principle at a State Islamic University in East Java, Indonesia, which refers to the definition and principles of OP according to experts, including Senge, 1990a; Senge, 1990b; Senge, 2000; Fullan, 1995, Silins and Mulford, 2002; Silins et al., 2002. The results of data analysis from documents, implementation observations and literature reviews, this Islamic university to some extent has met the qualifications as a learning organization by creating the concept of thinking and working collaboratively with the improvement of the character of collaborative leaders in each department. Although the transfer of leadership skills from high-ranking officials to lecturers as educational leaders has not been fully implemented optimally, the spirit of improving the management system in universities is increasing, along with the implementation of collaborative learning and the reframing of universities as learning organizations.